2002
DOI: 10.1210/jc.2002-020308
|View full text |Cite
|
Sign up to set email alerts
|

The Acid-Labile Subunit of Human Ternary Insulin-Like Growth Factor-Binding Protein Complex in Girls with Central Precocious Puberty before and during Gonadotropin-Releasing Hormone Analog Therapy

Abstract: The aim of the study was to evaluate serum acid-labile subunit (ALS) concentrations and their relationship with other parameters of the human ternary IGF-I-binding protein (IGFBP) complex in girls with central precocious puberty (CPP) before and after pharmacological arrest of puberty. We studied serum ALS, free IGF-I, total IGF-I, IGFBP-3 levels and IGFBP-3 protease activity in 13 girls, aged 1.6-7.8 yr (mean, 5.9 +/- 2.2), diagnosed as having CPP before and after 6 and 12 months of GnRH analog (GnRHa) therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Treatment of CPP with gonadotropin-releasing hormone analogs (GnRHa) stops pubertal development and slows growth velocity. In some studies, GH secretion was found to decrease with the decline of gonadal steroids (1,(3)(4)(5). Recently, the reduction of the IGF-I ternary complex formation was attributed to a reduction of ALS (acid-labile subunit of human ternary insulin like the growth factor-binding protein complex), whereas there was no change in IGF-I and IGF-binding protein (IGFBP)-3 levels (4).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of CPP with gonadotropin-releasing hormone analogs (GnRHa) stops pubertal development and slows growth velocity. In some studies, GH secretion was found to decrease with the decline of gonadal steroids (1,(3)(4)(5). Recently, the reduction of the IGF-I ternary complex formation was attributed to a reduction of ALS (acid-labile subunit of human ternary insulin like the growth factor-binding protein complex), whereas there was no change in IGF-I and IGF-binding protein (IGFBP)-3 levels (4).…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR assays indicate that IGFALS is expressed ubiquitously in pigs and transcripts are particularly abundant in the liver, lung, white adipose tissue, prostate, epididymis, thyroid and bladder. of IGFALS in serum (Cisternino et al 2002). The dysfunction of IGFALS has been implicated in a subtle impairment of linear growth, a delay in the onset and slow progress of puberty in a 17-year-old boy (Domene et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the important role of IGFALS in growth and development in mammals. For instance, girls with central precocious puberty, who are characterized for enhanced growth velocity and early puberty, have an increased level of IGFALS in serum (Cisternino et al. 2002).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Although the mechanisms underlying growth deceleration during GnRHa therapy are not completely understood, studies have demonstrated that it is not caused by changes to the growth hormone (GH)-insulin-like growth factor (IGF)-1 axis. [10][11][12][13][14][15][16][17][18] Recent studies have shown that the addition of GH to GnRHa increases the growth velocity and improves the final height in children with CPP as compared with GnRHa treatment alone. 9,12,15 It is suggested that the growth-promoting action of GH in CPP is, in part, somatotropic independent and may occur locally at the growth plate either directly or in cooperation with other growth factors.…”
Section: Introductionmentioning
confidence: 99%